2021
DOI: 10.1080/21645515.2021.1955611
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen years’ clinical experience and the first million babies protected with human live-attenuated vaccine against rotavirus disease in Italy

Abstract: Rotavirus (RV) causes up to half of hospital and community acute gastroenteritis (AGE) cases in young children in Italy. Two RV vaccines, available since 2006, are human RV (HRV) and human bovine RV (HBRV). This report looks back at the implementation of RV vaccination with HRV in Italy, and at HRV current and future perspectives. Initial regional policies led to national implementation by 2018, after scientific societies' disease awareness efforts. Following vaccination, RV hospitalizations declined significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…Nevertheless, research into the expanded benefits of RV vaccines on various clinical aspects is an ongoing and active area of study that needs to be increased and reinforced [ 33 ]. Lastly, it should be noted that our results could also have health economic implications: the reduction of AGE hospitalizations observed could represent a proxy for a large health-care cost savings attributable to RV vaccination, which was already found to be a cost-effective strategy from a health payer’s and societal perspective [ 28 ]. Previous economic analyses have shown that, in the absence of vaccination, RVGE would lead to increased healthcare costs and reduced quality of life in patients [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Nevertheless, research into the expanded benefits of RV vaccines on various clinical aspects is an ongoing and active area of study that needs to be increased and reinforced [ 33 ]. Lastly, it should be noted that our results could also have health economic implications: the reduction of AGE hospitalizations observed could represent a proxy for a large health-care cost savings attributable to RV vaccination, which was already found to be a cost-effective strategy from a health payer’s and societal perspective [ 28 ]. Previous economic analyses have shown that, in the absence of vaccination, RVGE would lead to increased healthcare costs and reduced quality of life in patients [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, the results of our study suggest a relationship between the reduction of AGE hospital discharges and the increase in RV vaccination coverage at the national level, as observed in previous regional experiences [ 25 , 26 ]. In Italy, before the introduction of universal RV vaccination in their regional immunization plans in 2017, the regions/AAPPs took different approaches to providing access to RV vaccination, following different regional policies [ 28 ]. Sicily, for example, was the first region to offer universal RV vaccination in 2013, followed by Calabria in 2015; Puglia introduced RV vaccination for all newborns at a discounted co-payment, whereas other regions offered free vaccination to defined categories of infants [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 , 5 Fifteen years after rotavirus vaccines were made available in Italy, more than one million babies have been protected with the two-dose human live-attenuated rotavirus vaccine. 6 Vaccination against rotavirus is included in the vaccination calendar of the National Vaccine Prevention Plan 2017–2019; it is offered free of charge to all newborns in their first year of life (two or three doses, depending on which of the two available vaccines is used). 7 , 8 Rotavirus vaccination is strongly recommended (as is vaccination against Neisseria meningitidis serogroup B and C and pneumococcal disease) but not mandatory.…”
Section: Introductionmentioning
confidence: 99%